2014
DOI: 10.1590/s1806-37132014000300011
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in hospitalized patients: clinical characteristics of patients receiving treatment within the first 24 h after admission

Abstract: Objective: To evaluate clinical characteristics and outcomes in patients hospitalized for tuberculosis, comparing those in whom tuberculosis treatment was started within the first 24 h after admission with those who did not. Methods: This was a retrospective cohort study involving new tuberculosis cases in patients aged ≥ 18 years who were hospitalized after seeking treatment in the emergency room. Results: We included 305 hospitalized patients, of whom 67 (22.0%) received tuberculosis treatment within the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…But neither of these studies has assessed post-discharge mortality. In a retrospective cohort study, Silva et al ( 15 ) evaluated new cases of TB treated in the emergency room of a university hospital and that required hospitalization. They included 305 patients with TB and described an in-hospital mortality of 16.4% and one-year mortality of 31.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But neither of these studies has assessed post-discharge mortality. In a retrospective cohort study, Silva et al ( 15 ) evaluated new cases of TB treated in the emergency room of a university hospital and that required hospitalization. They included 305 patients with TB and described an in-hospital mortality of 16.4% and one-year mortality of 31.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these hospitalizations relate to cases that are more severe ( 13 , 14 ). A retrospective cohort study of patients hospitalized for TB in Southern Brazil identified a one-year mortality of 31.8% in post-discharge subjects ( 15 ). Determining outcomes and the factors associated with them following discharge from TB hospitalization is crucial to better understand the potential impact of the disease, which may help establish health policies to improve survival.…”
Section: Introductionmentioning
confidence: 99%
“…TB does not usually require hospital admission for treatment, but if symptoms such as shortness of breath, and deterioration in a systemic condition are present, hospitalization may be necessary. A large proportion of patients with TB are hospitalized 8 , 9 , and estimates of in-hospital mortality range from 2% to 12% 10 14 ; most of the current costs of TB treatment result from hospitalization 15 .…”
Section: Introductionmentioning
confidence: 99%